Intensified treatment of patients with early stage, unfavourable Hodgkin lymphoma: long-term follow-up of a randomised, international phase 3 trial of the German Hodgkin Study Group (GHSG HD14). Issue 4 (April 2021) - Gillessen, Sarah; Plütschow, Annette; Fuchs, Michael; Markova, Jana; Greil, Richard; Topp, Max S; Meissner, Julia; Zijlstra, Josée M; Eichenauer, Dennis A; Bröckelmann, Paul J; Diehl, Volker; Borchmann, Peter; et al.
Summary: Background: To improve the long-term tumour control in early, unfavourable Hodgkin Lymphoma, the German Hodgkin Study Group (GHSG) HD14 trial compared four cycles of doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) with an intensified chemotherapy regimen consisting of two cycles of escalated bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, and prednisone (escalated BEACOPP) plus two cycles of ABVD. The final analysis of the trial showed a significant advantage in terms of freedom from treatment failure (difference 7·2% [95% CI 3·8–10·5] at 5 years) for patients who received two cycles of escalated BEACOPP and two cycles of ABVD. However, there was no difference in overall survival between the two groups. To evaluate long-term efficacy and toxicity of this strategy, we did a follow-up analysis. Methods: Patients aged 18–60 years with performance status of 2 or less and primary diagnosis of early, unfavourable Hodgkin lymphoma (all histologies) were included in an international, randomised, open-label, phase 3 trial. Patients were randomly assigned to receive four cycles of ABVD (ABVD group) or two cycles of escalated BEACOPP and two cycles of ABVD (2 + 2 group), both groups also received 30 Gy involved field radiotherapy. The ABVD dosing regimen was doxorubicin 25 mg/m 2 (days 1 and 15), bleomycin 10 mg/m 2 (days 1 and 15), vinblastine 6 mg/m 2 (days 1 and 15), and dacarbazine 375 mg/m 2 (days 1 and 15), repeated on day 29. The escalated BEACOPP dosing regimen was cyclophosphamide 1250 mg/m 2 (day 1), doxorubicin 35 mg/m 2 (day 1), etoposide 200 mg/m 2 (days 1–3), procarbazine 100 mg/m 2 (days 1–7), prednisone 40 mg/m 2 (days 1–14), vincristine 1·4 mg/m 2 (day 8; maximum 2 mg), and bleomycin 10 mg/m 2 (day 8), repeated on day 22. After closure of the ABVD group according to prespecified rules, patients were assigned to receive two cycles of escalated BEACOPP and two cycles of ABVD (non-randomised 2 + 2 group), which continued until the end of the predefined 5-year recruitment period. In this prespecified long-term follow-up analysis, we aimed to evaluate the secondary endpoints progression-free survival, overall survival, and long-term toxicity. To this end, we did a descriptive intention-to-treat analysis of all qualified HD14 patients and on the predefined subsets of randomised qualified HD14 patients and patients in the non-randomised 2 + 2 group. The trial was registered on the International Standard Randomised Controlled Trial database, 04761296. Findings: Between Jan 28, 2003, and Dec 29, 2009, 1686 patients were randomly assigned to the ABVD group (847 [50·2%] patients) and the 2 + 2 group (839 [49·8%] patients). 370 additional patients were recruited to the non-randomised 2 + 2 group. 1550 (92%) randomly assigned patients (median observation time 112 months [IQR 80–132]) and 339 (92%) patients in the non-randomised 2 + 2 group (median observation time 74 months [58–100]) were included in the qualified analysis set. 10-year overall survival in the randomly assigned patients was 94·1% (95% CI 92·0–95·7) for the ABVD group and 94·1% (91·8–95·7) for the 2 + 2 group (HR 1·0 [95% CI 0·6–1·5]; p=0·88). 8-year overall survival in the non-randomised 2 + 2 group was 95·1% (95% CI 91·6–97·2). 10-year progression-free survival in the randomly assigned patients was 85·6% (95% CI 82·6–88·1) for the ABVD group and 91·2% (88·4–93·3) for the 2 + 2 group (HR 0·5% [95% CI 0·4–0·7]; p=0·0001), accounting for a significant difference of 5·6% (95% CI 1·9–9·2) favouring the 2 + 2 group (p=0·0001). In the non-randomised 2 + 2 group, 8-year progression-free survival was 94·5% (95% CI 91·1–96·6). Standardised incidence ratios of second primary malignancies were similar between the ABVD group (2·3 [95% CI 1·6–3·1]) and the 2 + 2 group (2·5 [1·8–3·4]; Gray's p=0·80). Standardised incidence ratio of second primary malignancies was 3·1 (95% CI 1·7–5·0) in the non-randomised 2 + 2 group. Interpretation: This long-term analysis confirms superior tumour control in the 2 + 2 group compared with the ABVD group without translating into an overall survival difference. At longer follow-up, there is no difference regarding second primary malignancies between groups. In conclusion, the 2 + 2 regimen spares a significant number of patients from the burden of relapse and additional treatment without increased long-term toxicity. Funding: Deutsche Krebshilfe eV and Swiss Federal Government.